ANALISIS KARBOHIDRAT PADA BISKUIT AMPAS KELAPA: Carbohydrate analysis of coconut dregs biscuits - Gunawan Gunawan; Rini Fertiasari (PAKIS JOURNAL INSTITUTE, 2023)
Coconut dregs is an organic waste that comes from the process of squeezing coconut milk or making VCO. Coconut dregs are only disposed of as garbage and sometimes become animal feed. The nutritional values ​​ of coconut pulp include crude fiber, carbohydrates, crude protein, and crude fat. The purpose of this study was to determine the macronutrient content of carbohydrates, proteins, fats, and reducing sugars in coconut dregs biscuits. The coconut pulp was dried in an oven for 5 h at a temperature of ± 700 C and dried for 3 days, in one day for 5 hours. Dried coconut dregs were floured and sifted using a 40-mesh sieve. Coconut dregs flour which is substituted with wheat flour and adding other ingredients, biscuit dough that has been molded, is baked at a temperature of 1000 C for 1.5 hours. Based on the results of the research on coconut dregs biscuits, it was shown that the coconut dregs biscuits, both oven and drying methods, affect carbohydrates.